Volume expansion of a 413.5-m Mizuho core after its recovery - Nakawo, Masayoshi (1986)
P(論文) The density of the core samples was measured soon after their recovery, and the measurement was repeated 1,3,6 and 27 months later. It was found that the density decreased significantly with time. The decreasing rate increased with depth, and decreased with time. The data have been analyzed on the basis of a stress-strain relationship, ε=K(Δp)^n, where ε is the strain rate and Δp is the difference between the pressures of contained bubbles and of the atmosphere. It was found that n≈3,which is a generally accepted value. The value of K was found, on the other hand, of the order of (10)^<-10> s^<-1> MPa^<-3> for a temperature of -10℃, which is much smaller than those obtained previously under deviated stress conditions. departmental bulletin paper